APLIKASI FORMULASI PUPUK ORGANIK UNTUK EFISIENSI PENGGUNAAN PUPUK ANORGANIK NPK PHONSKA PADA TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Tumewu, P.; Montolalu, M.; Tulungen, A. G. (EUGENIA, 2017)
ABSTRACT The aim of this research is to know the effect of organic fertilizer formulation and NPK Phonska fertilizer on the growth and yield of sweet corn, and to get organic fertilizer formulation for the efficiency of inorganic fertilizer NPK Phonska in increasing the yield of sweet corn. The factorial experiment was designed using a Randomized Block Design consisting of two factors. Factor I (A) = Formulation of Organic Fertilizer, consisting of A1 = Water hyacinth, Cow Manure, chicken manure, A2 = Hydrilla verticillata, cow dung, chicken manure, A3 = Kirinyuh, cow dung, chicken manure. Factor II (B) = Phonska fertilizer, Consist of B1 = 25% Phonska, B2 = 50% Phonska, B3 = 75% Phonska, B4 = 100% Phonska. Each treatment was repeated three times to obtain 36 experimental plots. Response variables observed included: Plant dry weight, Length of cob, Cob diameter, Weight of cob, measured at harvest. Data were analyzed using variance analysis and if there was effect of treatment continued by using Test of Honest Real Difference (BNJ) at 5% test level. The results showed that the interaction between organic fertilizer formulation and NPK phonska significantly affect the diameter of cob and sweet corn cob weight. The dry weight of sweet corn plant is influenced by organic fertilizer formulation. Formulation of organic fertilizer Hydrilla verticillata + cow dung + chicken dung 20 ton / ha dose able to reduce the dose of NPK Phonska at half of the recommended dosage.Keywords: formulation of organic fertilizer, sweet corn yield, Phonska  ABSTRAK Penelitian bertujuan untuk mengetahui pengaruh interaksi formulasi pupuk organik dan pupuk NPK Phonska terhadap pertumbuhan dan hasil jagung manis, serta mendapatkan formulasi pupuk organik untuk efisiensi pupuk anorganik NPK Phonska dalam meningkatkan hasil jagung manis. Percobaan factorial  dirancang menggunakan Rancangan Acak Kelompok yang terdiri dari dua faktor. Faktor I (A) = Formulasi Pupuk Organik, terdiri dari A1 = Eceng gondok, Kotoran sapi, kotoran ayam, A2 = Hydrilla verticillata, kotoran sapi, kotoran ayam, A3 = Kirinyuh, kotoran sapi, kotoran ayam. Faktor II(B) =  Pupuk Phonska, Terdiri dari B1 = 25% Phonska, B2 = 50% Phonska, B3 = 75% Phonska, B4 = 100 % Phonska. Setiap perlakuan diulang tiga kali sehingga diperoleh 36 petak percobaan. Variabel respons yang diamati  meliputi : Berat kering tanaman, Panjang tongkol, Diameter tongkol, Bobot tongkol, diukur pada saat panen. Data  dianalisis menggunakan  analisis ragam dan jika terdapat pengaruh perlakuan dilanjutkan dengan menggunakan Uji Beda Nyata Jujur (BNJ) pada taraf uji 5 %. Hasil penelitian  menunjukkan bahwaInteraksi antara formulasi pupuk organik dan NPK phonska berpengaruh nyata terhadap diameter tongkol dan  bobot tongkol jagung manis. Bobot kering tanaman jagung manis dipengaruhi oleh  formulasi pupuk organik.  Formulasi pupuk organik Hydrilla verticillata+ kotoran sapi+kotoran ayam dosis 20 ton/ha mampu menurunkan dosis NPK Phonska setengah dari dosis rekomendasi.Kata kunci: formulasi pupuk organik, hasil jagung manis, Phonska